Preservation of Dodol Moyog as a Gastronomic Tourist Attraction in Cirebon Regency - Darwis, Riadi; Nur Baity, Mutiara Rizky (Gastronomy Tourism Journal, 2021)
Dodol moyog, a snack that has a unique name, is a traditional food originating from Cirebon Regency which is currently very rare to find, even many local people do not know the dodol moyog snack itself. This study aims to determine the gastronomic concept of dodol moyog including history, philosophy, tradition, social, and to analyze the method of cooking the traditional Cirebon regency snack, the equipment used and the manufacturing standards, and efforts to preserve dodol moyog. The research method used is a qualitative method, while the data collection technique is done by interviewing, observing, studying literature and studying documentation. The result of this research is that no one knows for sure how the history of dodol moyog is called dodol moyog because in the process of making it in â€œoyog-oyogâ€ or stirred. The ingredients used to make dodol moyog are tapioca flour, brown sugar, salt and water. While the ingredients for making â€œmata ulaâ€ are coconut milk and sugar. Support from various parties is needed in the development of the dodol moyog business so that it can attract tourists to make dodol moyog a gastronomic tourism destination in Cirebon Regency.